Viral Causality of Human Cancer and Potential Roles of Human Endogenous Retroviruses in the Multi-Omics Era: An Evolutionary Epidemiology Review - Kitsou, Konstantina; Iliopoulou, Maria; Spoulou, Vana; Lagiou, Pagona; Magiorkinis, Gkikas (Frontiers in Oncology, 2021)
Being responsible for almost 12% of cancers worldwide, viruses are among the oldest known and most prevalent oncogenic agents. The quality of the evidence for the in vivo tumorigenic potential of microorganisms varies, thus accordingly, viruses were classified in 4 evidence-based categories by the International Agency for Research on Cancer in 2009. Since then our understanding of the role of viruses in cancer has significantly improved, firstly due to the emergence of high throughput sequencing technologies that allowed the “brute-force” recovery of unknown viral genomes. At the same time, multi-omics approaches unraveled novel virus-host interactions in stem-cell biology. We now know that viral elements, either exogenous or endogenous, have multiple sometimes conflicting roles in human pathophysiology and the development of cancer. Here we integrate emerging evidence on viral causality in human cancer from basic mechanisms to clinical studies. We analyze viral tumorigenesis under the scope of deep-in-time human-virus evolutionary relationships and critically comment on the evidence through the eyes of clinical epidemiology, firstly by reviewing recognized oncoviruses and then by examining the potential role of integrated viruses in our genome in the process of carcinogenesis.